Comparison of PD-L1 protein expression between primary tumors and metastatic lesions in triple negative breast cancers. Issue 2 (25th November 2020) - Rozenblit, Mariya; Huang, Richard; Danziger, Natalie; Hegde, Priti; Alexander, Brian; Ramkissoon, Shakti; Blenman, Kim; Ross, Jeffrey S; Rimm, David L; Pusztai, Lajos
Abstract : Programmed Death Ligand 1 (PD-L1) positivity rates differ between different metastatic sites and the primary tumor. Understanding PD-L1 expression characteristics could guide biopsy procedures and motivate research to better understand site-specific differences in the tumor microenvironment. The purpose of this study was to compare PD-L1 positivity on immune cells and tumor cells in primary and metastatic triple negative breast cancer (TNBC) tumors. Retrospective study utilizing the PD-L1 database of Foundation Medicine containing the SP142 companion diagnostic immunohistochemistry assay (SP142 CDx) and Food and Drug Administration guidelines for scoring. 340 TNBC cases (179 primary tumors and 161 unmatched metastatic lesions) were evaluated. The primary outcome measures were PD-L1 positivity rates in immune cells and tumor cells. χ 2 test was used for comparisons. Spearman's correlation coefficient was used for correlations. More primary tumors were positive for PD-L1 expression on immune cells than metastatic lesions (114 (63.7%) vs 68 (42.2%), p<0.0001). This was driven by the lower PD-L1 positivity rates in skin (23.8%, 95% CI: 8.22% to 47.2%), liver (17.4%, 95% CI: 5.00% to 38.8%) and bone (16.7%, 95% CI: 2.10% to 48.4%) metastases. Lung (68.8%, 95% CI: 41.3% to 90.0%), soft tissues (65.2%, 95% CI: 42.7% to 83.6%) and lymph nodes (51.1%, 95% CI: 35.8% to 66.3%) had PD-L1 % positivity rates similar to primary tumors. PD-L1 expression was rare on tumor cells in both the breast and metastatic sites (8.3% vs 4.3%, p=0.13). The rate of PD-L1 positivity varies by metastatic location with substantially lower positivity rates in liver, skin and bone metastases compared with primary breast lesions or lung, soft tissue or lymph node metastases. This difference in PD-L1 positivity rates between primary tumors and different metastatic sites should inform physicians when choosing sites to biopsy and suggests a difference in the immune microenvironment across metastatic sites.